2019
DOI: 10.1016/j.intermet.2019.106582
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co on the phase stability of CrMnFeCoxNi high entropy alloys following long-duration exposures at intermediate temperatures

Abstract: The effect of Co on the phase stability of the CrMnFeCoxNi family of alloys, where the atomic ratio x = 0, 0.5, 1.5, has been experimentally established following 1000 hour heat treatments at 700 and 900˚C and up to 5000 hours at 500˚C. All the alloys were single phase fcc in the homogenised condition, except for CrMnFeNi which also contained bcc precipitates that remained present following exposures at 900˚C and 700˚C. The exposures at 900˚C and 700˚C also resulted in the formation of phase precipitates in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 52 publications
2
12
1
Order By: Relevance
“…Depending on composition and processing routes, HEAs exhibit variations in their phase constitution and microscopic morphology [20]. Several HEA systems based on Cr, Mn, Fe, Co, Ni and Al were proposed to be single-phase face-centered cubic (fcc) structures in quite broad compositional and temperature intervals [21][22][23]. The equiatomic CrMnFeCoNi HEAthe classical Cantor alloyforms a stable fcc solid solution above ~800 °C that can be retained down to room temperature (RT), if the alloy is cooled at a sufficiently high rate [24,25], whereas AlxCrFeCoNi HEAs for x < 0.3 are fcc at RT after cooling rapidly from above 1000 °C [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on composition and processing routes, HEAs exhibit variations in their phase constitution and microscopic morphology [20]. Several HEA systems based on Cr, Mn, Fe, Co, Ni and Al were proposed to be single-phase face-centered cubic (fcc) structures in quite broad compositional and temperature intervals [21][22][23]. The equiatomic CrMnFeCoNi HEAthe classical Cantor alloyforms a stable fcc solid solution above ~800 °C that can be retained down to room temperature (RT), if the alloy is cooled at a sufficiently high rate [24,25], whereas AlxCrFeCoNi HEAs for x < 0.3 are fcc at RT after cooling rapidly from above 1000 °C [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The light-contrast precipitates contained around 45 at.% Cr and were equally depleted of Mn, Fe and Co relative to the matrix, but contained only ~ 5 at.% Ni. This composition is indicative of the σ phase, which has been widely observed in alloys of the CrMnFeCoNi system [6][7][8][9]11,26,46]. The dark-contrast precipitates, on the other hand, contained ~ 70 at.% Cr and less than 10 at.% of the other elements (C was omitted from quantification as SEM-EDX is unreliable for measuring the concentration of light elements).…”
Section: Crmnfe15conimentioning
confidence: 89%
“…However, when these predictions are extended to higher order systems, the model parameters often require adjustment to accurately describe the Gibbs energies and hence equilibrium phase stability [24]. In particular, it has been observed that predictions often fail to accurately describe the extent to which intermetallic phases persist into multicomponent space [12,[26][27][28]. Therefore, the use of appropriate experimental data in the development of CALPHAD databases is essential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] In general, N should be not less than 4 to meet the requirement of ΔS c > R. According to the crystallographic knowledge, the initially proposed high-entropy alloy (HEA) can be considered as a solid solution, which is formed by substituting the transition metals or metals for pure metal with equiatomic or near-equiatomic ratios ranging from 5 to 35 at%. The composition design of HEA is initially focused on the solid solution of pure metal with equiatomic ratio at metal crystal site, such as face-centered-cubic (FCC)-based CoCrFeMnNi and CrMnFeNiCo x ; [3,4] body-centered-cubic (BCC)-based HfNbTaTiZr and NbMoTaVW; [5,6] and hexagonal-closepacked (HCP)-based GdDyTbLuY and HoDyYGdTb. [7][8][9] HEAs show excellent mechanical and physical properties such as high strength and ductility, [10,11] good corrosion resistance, [12,13] excellent cryogenic and high temperature performance.…”
Section: Introductionmentioning
confidence: 99%